Pemanfaatan Tanaman Refugia untuk Mengendalikan Hama Tanaman Padi di Desa Simbang Kabupaten Maros - Mustarin, Amirah; Rauf, Reski Febyanti; Patang; Wiharto, Muhammad; Asrijal (Jurusan Teknik Informatika dan Komputer, 2023)
PKM utilization of refugia plants to control paddy pests is a simple technology implemented to answer the problem of difficulties in controlling pests without the use of pesticides in Maros Regency. The utilization of refugia plants in ecological engineering is a crucial component of integrated pest control (IPM) technology. Its primary objective is to establish a biological balance between pests and natural enemies, ensuring that pest populations remain below the economic threshold. Habitat engineering, achieved through the strategic planting of refugia in paddy fields, offers spatial and/or temporal shelter for natural enemies, such as predators and parasitoids. Additionally, it supports various components of biotic interactions in ecosystems, including vital pollinators. Furthermore, certain refugia plants possess the potential to serve as effective biological agents for controlling pests in paddy plants. The resulting products consist of knowledge regarding integrated pest control (IPM) and refugia planting in paddy fields. This PKM (Community Service Program) is carried out in two stages, namely the training stage, which lasts for one day, and the practical stage involving farmer groups and assistance. Zinnia flowers and kenikir flowers are types of refugia plants that were introduced to the partner group in Simbang Village, Maros Regency. The use of kenikir plants and ziinia plants in paddy fields is proven to minimize the use of synthetic pesticides. A group of partners will conduct rice planting with refugia plant pest control, starting with the cultivation of refugia plants to meet the needs of farmer groups.